Proceedings of ISSRE '96: 7th International Symposium on Software Reliability Engineering
DOI: 10.1109/issre.1996.558896
|View full text |Cite
|
Sign up to set email alerts
|

Detection of software modules with high debug code churn in a very large legacy system

Abstract: Socaety has become so dependent on relaable telecommunacataons, that faalures can rask loss of emergency servace, busaness dasruptaons, or asolataon from fraends. Consequently, telecommunacataons software as requared t o have hagh relaabalaty. Many prevaous studaes define the classaficataon fault-prone an terms of fault counts. Thas study defines fault-prone as exceedang a threshold of debug code churn, defined as the number of lanes added or changed due t o bug fixes. Prevaous studaes have characterazed reuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 20 publications
(5 reference statements)
1
37
0
Order By: Relevance
“…Khoshgoftaar et al (1996) classified modules as defect-prone based on the number of past modifications to the source files composing the module. They showed that the number of lines added or removed in the past is a good predictor for future defects at the module level.…”
Section: Related Work In Defect Predictionmentioning
confidence: 99%
“…Khoshgoftaar et al (1996) classified modules as defect-prone based on the number of past modifications to the source files composing the module. They showed that the number of lines added or removed in the past is a good predictor for future defects at the module level.…”
Section: Related Work In Defect Predictionmentioning
confidence: 99%
“…SCC, as used in this study, falls under this category. Among the first to study the relation between code churn defined as LM and Bugs was [17]. Work carried out in [25] explored the extent to which the use of relative code churn measures, e.g., LM weighted by total lines of code, outperformed absolute measures when predicting defect density: In Windows Server 2003, absolute churn measures showed a lower performance compared to relative ones.…”
Section: Related Workmentioning
confidence: 99%
“…We also note that machine learning has, in the past, been used for defect prediction, typically by training on data from source code repositories (e.g., [7,17,23,25]). We believe that machine learning has substantial advantages over traditional statistics and that much room yet exists for the exploitation of such techniques in the domains of Software Engineering and Programming Languages.…”
Section: Related Workmentioning
confidence: 99%